Problematika Administrasi Peserta Didik dalam Era Society 5.0 : Mengintegrasikan Teknologi untuk Meningkatkan Kualitas Pendidikan - Abda Muhammad Al Furqan; Nazila Qirani; Ahmad Sabri; Rully Hidayatullah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This article discusses the crucial role of student administration within the context of education in the Society 5.0 era, where technology has become an integral part of the learning process. The research employs a library research method to gather and analyze various literature sources related to student administration, the role of teachers, and the use of technology in education. The findings indicate that the success of student administration relies not only on technology but also on the collaboration between teachers, students, parents, and other stakeholders. By utilizing digital tools and information systems, teachers can enhance efficiency in managing student data, assessments, and other administrative processes. This article aims to provide significant contributions to the development of more effective and efficient student administration, ultimately improving the overall quality of education in the digital era.